Coarse-Grained Simulation of Mechanical Properties of Single Microtubules With Micrometer Length - Zha, Jinyin; Zhang, Yuwei; Xia, Kelin; Gräter, Frauke; Xia, Fei (Frontiers in Molecular Biosciences, 2021)
Microtubules are one of the most important components in the cytoskeleton, and play a vital role in maintaining the shape and function of cells. Because single microtubules are some micrometers long, it is difficult to simulate such a large system using an all-atom model. In this work, we use the newly developed convolutional and K-means coarse-graining (CK-CG) method to establish an ultra-coarse-grained (UCG) model of a single microtubule, on the basis of the low electron microscopy density data of microtubules. We discuss the rationale of the micro-coarse-grained microtubule models of different resolutions, and explore microtubule models up to 12 microm length. We use the devised microtubule model to quantify mechanical properties of microtubules of different lengths. Our model allows mesoscopic simulations of micrometer-level biomaterials and can be further used to study important biological processes related to microtubule function.